Mobilitas Animi: Improvising Technologies, Intending Chance. - Lewis, George E. (Parallax)
An essay is presented discussing how technology and improvisation relate to knowledge and meaning. The author suggests improvisation is an essential component of everyday life. The use of computers in music had led to a rise in improvisation and interactive composition. The Live Algorithms for Music (LAM) research group has studied the collaboration of creative machines and musicians through algorithms.